iOS 15 SwiftUI 3 loan tracker MVVM, CoreData, and cloud kit (Packt Publishing, 2021)
Learn to build a Loan Tracker app SwiftUI3.0, MVVM, Combine, and CoreData. About This Video Understand how to set the navigation title and customizing the UI Learn EditPayment functions and cloud kit Understand how to delete an item and loading view In Detail SwiftUI 3 is one of the most popular tools for building iOS applications. In this course you will learn how to use SwiftUI features and coding to build a robust application for loan tracking. The course is focused on data passing and structuring for SwiftUI. We will use MVVM pattern to develop an application that will use CoreData and CloudKit to save, read, update, and delete data from the CoreData and CloudKit. We will also add some custom calculations and visual interfaces to sort our payments and provide information on the loan. By taking this course, you will learn how to pass data around our application and how to make the core part of our application work. We will use model view pattern to build the application and use Cloudkit in order to sync our local database with the cloud. By the end of this course, you will gain a good understanding of SwiftUI and will be able to build modern and reliable iOS apps. Who this book is for This course is for anyone who has a basic understanding of using SwiftUI to make UI and is interested in learning the process of making the app function.